Filamentous rods in the cerebrospinal fluid of a child with ventriculoperitoneal shunt: “Separation Anxiety” at the microscopic level! - Buckley, Kaila; Feldman, Alex; Kahwash, Samir (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Certain bacteria and antibiotic combinations can result in unusual morphologic transformations such as the creation of septate filamentous bacterial rods, where division is preserved, but separation is inhibited. This is often seen when subinhibitory concentrations of antibiotics are administered. Herein, we describe this phenomenon in the case of a teenage boy with an infected ventriculoperitoneal shunt, whose culture-proven Pseudomonas aeruginosa took on a filamentous appearance following antibiotic treatment. This transformation is important to recognize, so it is not misconstrued as fungal hyphae, committing the patient to unnecessary treatment.
Keywords: Antibiotic-mediated bacterial filamentation; filamentous rods; Pseudomonas aeruginosa